The Communication Style of Influencers in Building Interaction With Followers @Thifalislami - Luhur Iran Pangestu; Siti Khumayah; Welly Wihayati (ann4publisher@gmail.com, 2026)
Background. Advances in communication technology have propelled social media into a primary space for information exchange and the formation of digital relationships. In this context, influencers play a strategic role in fostering interactions with their audience through communication patterns on Instagram. This study stems from the scarcity of research that specifically examines the communication styles of micro-influencers, particularly in their efforts to create sustainable interactions with followers. Aims. This study aims to examine communication styles and interaction forms, and to identify the most prominent communication style on the Instagram account @thifalislami. Methods. The method used is a descriptive qualitative approach with data collection techniques including in-depth interviews, non-participant observation, and documentation. Informants were selected through purposive sampling, involving the influencer as the primary informant and several followers as supporting informants. Data analysis was conducted using an interactive model encompassing data reduction, data presentation, and drawing conclusions. Result. The results of the study indicate that influencers employ communication styles that are friendly, open, relaxed, expressive, and animated, with the “open” style being the most dominant. Conclusion. Interactions are built through posted content, captions, comment sections, and the “Story” feature, which helps foster authentic and sustained relationships with followers.